Twórczość poetycka Nikołaja Kynczewa w Bułgarii i Polsce - Gołek-Sepetliewa, Dorota (Przekłady Literatur Słowiańskich, 2022)
This article presents analyses and interpretations of the work of the Bulgarian poet Nikolay Kanchev (1936—2007), collected in the Polish-language volume Against the Absence (2020), translated by Wojciech Gałązka. It takes into account the critical context of the Polish and Bulgarian reception of Nikolay Kanchev’s poetry. The presence of Nikolay Kanchev’s work in Poland since the 1980s is possible thanks to the long-standing efforts of his translator, Wojciech Gałązka. In his homeland, the poet experienced the censorship’s rejection of his first two volumes Presence (1965) and As a Mustard Seed (1968), many years of silence (1968—1980), and a successful but belated reception since the 1990s. A review of historical-literary studies makes it possible to identify the ideological and aesthetic choices of Kanchev’s poetry — neoclassicism, metarealism, conceptualism, philosophical intellectualism, laconicism, and paradoxicality.